"On paper" and "having papers": Zimbabwean migrant women's experiences in accessing healthcare in Giyani, Limpopo province, South Africa. Issue 1 (2nd January 2018) - Chekero, Tamuka; Ross, Fiona C.
Abstract : South Africa is signatory to international protocols that secure migrant rights to healthcare. Its national health policy prohibits discrimination. Pregnant women and children under six years ostensibly enjoy access to free healthcare, irrespective of migration status. What is clear "on paper, " however, becomes considerably more opaque when experienced by those who do not "have papers." We explore this in Giyani, South Africa, an important migrant destination. Despite a progressive healthcare policy and immigrant rights regime, migrant women's lack of proper documentation precludes them in practice from accessing state-provided reproductive healthcare. The result is twofold. Women who are entitled to public healthcare prefer to make use of private healthcare, despite the costs, and they make recourse to a range of extra-state relations for healthcare. We focus on one unexpected consequence: that the same healthcare providers who have formally refused access to state institutions may be available to migrants through personal networks, such as in churches. Here, medical care is seen as taking place in a religious register. The difference between what is "on paper" and "what papers migrants have" is critical but may be mediated by access to other realms of the social.